Historical aspects of probiotic use to prevent necrotising enterocolitis in preterm babies. (August 2019) - Jarrett, Prudence; Meczner, Andras; Costeloe, Kate; Fleming, Paul
Abstract: Over the last few decades, numerous studies have evaluated probiotic use for the prevention of necrotising enterocolitis in preterm babies. Early 'proof of concept' studies evaluating whether probiotics are capable of colonising the preterm gut have translated into multiple observational studies, small and large randomised controlled trials. Some show evidence of benefit while others have produced disappointing results. In this paper, we review the history of probiotic use in preterm babies for NEC prevention in an attempt to explain why uncertainty exists and why this intervention has not been universally adopted into routine neonatal practice.